2005
DOI: 10.1161/01.str.0000149625.99732.69
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Manifestations, and Predictors of Worsening White Matter on Serial Cranial Magnetic Resonance Imaging in the Elderly

Abstract: Background and Purpose-Magnetic resonance imaging (MRI) scans in the elderly commonly show white matter findings that may raise concerns. We sought to document incidence, manifestations, and predictors of worsening white matter grade on serial imaging. Methods-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
341
8
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(407 citation statements)
references
References 17 publications
33
341
8
3
Order By: Relevance
“…Longstreth et al (2005), for example, showed that subjects with worsening white matter grade experienced a greater decline on the Digit Symbol Substitution Test (Smith, 1973) than did subjects with no change in white matter grade. The mechanisms underlying this effect are not clear but potentially include disruption of frontal-subcortical circuits (Cummings, 1998;Owen, 2004), cortical atrophy secondary to deinervation, or concomitant microvascular changes in the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longstreth et al (2005), for example, showed that subjects with worsening white matter grade experienced a greater decline on the Digit Symbol Substitution Test (Smith, 1973) than did subjects with no change in white matter grade. The mechanisms underlying this effect are not clear but potentially include disruption of frontal-subcortical circuits (Cummings, 1998;Owen, 2004), cortical atrophy secondary to deinervation, or concomitant microvascular changes in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical and frontal lobe atrophy have also been shown to correlate with global cognition and measures of executive functioning (Raz, Williamson, Gunning-Dixon, Head, & Acker, 2000). A significant association has been established between white matter signal hyperintensities and cognition in several studies (Baum, Schulte, Girke, Reischies, & Felix, 1996;Breteler et al, 1994;Cook et al, 2004;DeCarli et al, 2005;De Groot et al, 2002;Fukui, Sugita, Sato, Takeuchi, & Tsukagoshi, 1994;Kovari et al, 2004;Kramer, Reed, Mungas, Weiner, & Chui, 2002;Longstreth et al, 2005;Matsubayashi, Shimada, Kawamoto, & Ozawa, 1992;Ylikoski et al, 2000) but not in others (Boone et al, 1992;Burns et al, 2005;Fein et al, 2000;Wahlund, Almkvist, Basun, & Julin, 1996). Similarly, the role of lacunae in cognition has not been well defined, with some studies showing a negative relationship between lacunae and cognition (Gold et al, 2005;Kramer et al, 2002;Longstreth et al, 2005;Price et al, 1997), whereas others have not, particularly when accounting for the presence of other important pathological markers, such as white matter disease (Fein et al, 2000;Mungas et al, 2001).…”
mentioning
confidence: 99%
“…31 We have shown that progression of PV WMH volume is associated with increased gait slowing over time. The relationship between increased rate of WMH burden and worse performance on gait testing over time has been reported, 15,32 although previous studies did not examine the potential differential relationships between subcortical and PV WMH volume change and progressive gait dysfunction. Increased progression of subcortical WMH lesions was associated with increased rate of memory decline, independent of cerebral or hippocampal atrophy.…”
Section: Figurementioning
confidence: 99%
“…In the Austrian Stroke Prevention Study, WMH levels increased steadily over 6 years, and while cognition was stable at 3 years (Schmidt et al 1999), it was significantly impaired after 6 years (Schmidt et al 2005; also see Prins et al 2005). The longitudinal increase of WMH can negatively affect several cognitive domains (Longstreth et al 2005), including executive function, with an increase of subcortical WMH ) and mental processing speed, when accompanied by an increase in periventricular WMH (van den Heuvel et al 2006). A high baseline level of WMH in deep and periventricular WM was most predictive of a longitudinal progression of WMH in the elderly (Sachdev et al 2007).…”
Section: Longitudinal Imaging Studies In Humansmentioning
confidence: 99%